Top Management Teams Diversity on Firm Performance in the COVID-19 Pandemic: Evidence from Indonesia - Kwikamto, Arya; Rudyanto, Astrid; Rahayuningsih, Deasy Ariyanti; Ponziani, Regi Muzio; Widayati, Nurti (Journal of Accounting Research, Organization and Economics, 2025)
Objective This research aims to analyze the effect of top management teams diversity on firm performance during COVID-19 pandemic. Top management teams diversity consists of cultural diversity, gender diversity and other diversities (tenure, network, scale, age).Design/Methodology This paper used mixed-method for data collection and data analysis. For quantitative method, this paper used 92 consumer cyclicals and consumer non-cyclicals companies listed in Indonesia Stock Exchange from 2020-2022, resulting in 275 observations that met the criteria. Random effect multiple regression is used to test the hypotheses. For qualitative method, this paper interviewed 5 human resources managers from consumer cyclicals and consumer non-cyclicals companies from various characteristics.Results The results show that top management teams scale and age positively influence the firm performance in consumer cyclical and consumer non-cyclical companies in Indonesia. Top management teams network has positive influence on firm performance in consumer cyclical companies, but negative influence on firm performance in consumer non-cyclical companies in Indonesia. On the other hand, cultural diversity, gender diversity, and top management teams tenure do not influence the firm performance in consumer cyclical and consumer non-cyclical companies in Indonesia.Research limitations/implications It can be implied that companies should tailor their leadership development and recruitment strategies to foster the most impactful forms of diversity to conquer the crisis.Novelty/Originality This research analyzes the effect of top management teams diversity in an emerging country during pandemic which fills the research gap.